Effects of online mindfulness-based interventions on the mental health of university students: A systematic review and meta-analysis - Gong, Xiao-Gang; Wang, Le-Peng; Rong, Guang; Zhang, Dao-Ning; Zhang, A-Yuan; Liu, Chao (Frontiers in Psychology, 2023)
Objectives: Mental health problems among university students are a cause of widespread concern. Mindfulness-based interventions (MBIs) delivered online have considerable potential to help university students manage mental health challenges. However, there is no consensus regarding the efficacy of online MBIs. This meta-analysis aims to determine whether MBIs are feasible and effective for improving university students’ mental health. Methods: Randomized controlled trials (RCTs) in Web of Science, PubMed, Cochrane Library, Embase and the US National Library of Medicine (Clinical Trial Registry) published through August 31, 2022, were searched. Two reviewers selected the trials, conducted a critical appraisal, and extracted the data. Nine RCTs met our inclusion criteria. Results: This analysis showed that online MBIs were effective in improving depression (standardised mean difference [SMD] = -0.27; 95% confidence interval [CI], -0.48 to -0.07; P = 0.008), anxiety (SMD = -0.47; 95% CI, -080 to -0.14; P = 0.006), stress (SMD = -0.58; 95% CI, -0.79 to -0.37; P < 0.00001), and mindfulness (SMD = 0.71; 95% CI, 0.17 to 1.25; p = 0.009) in university students. No significant effect was found on well-being (SMD = 0.30; 95% CI, -0.00 to 0.60; P = 0.05). Conclusion: The findings indicated that online MBIs could effectively improve the mental health of university students. Nevertheless, additional rigorously designed RCTs are required.